2022
DOI: 10.1177/01454455221129993
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Schedule Thinning on Student Behavior During the Caught Being Good Game

Abstract: The Caught Being Good Game (CBGG) is a classroom management intervention which is described as a variation of the classic Good Behavior Game (GBG). It is based on the principle of positive reinforcement, such that teams of students can earn points for following the class rules during the game. Points are awarded by the teacher at different intervals during the game and these intervals were the focus of the current study. We aimed to determine if the CBGG is effective with an initially dense schedule of reinfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Research has shown that symptoms associated with ADHD, such as hyperactivity, inattention, and impulsivity, often manifest as behavioral and academic problems (e.g., disruptions and poor academic engagement) which can negatively impact children’s academic outcomes (Barkley, 2018; DuPaul et al, 2014). It has been shown that the CBGG has been effective in reducing DB and improving academic engagement (Bohan et al, 2021, 2022; Bohan & Smyth, 2022, 2023). Therefore, the CBGG might help students diagnosed with ADHD in their learning process in the classroom settings.…”
mentioning
confidence: 99%
“…Research has shown that symptoms associated with ADHD, such as hyperactivity, inattention, and impulsivity, often manifest as behavioral and academic problems (e.g., disruptions and poor academic engagement) which can negatively impact children’s academic outcomes (Barkley, 2018; DuPaul et al, 2014). It has been shown that the CBGG has been effective in reducing DB and improving academic engagement (Bohan et al, 2021, 2022; Bohan & Smyth, 2022, 2023). Therefore, the CBGG might help students diagnosed with ADHD in their learning process in the classroom settings.…”
mentioning
confidence: 99%